RUSSIAN RAILWAYS AT THE TURN OF THE CENTURY (SITUATIONAL ANALYSIS) - V. Persianov; A. Zhdanov (Вестник университета)
The article discusses the situation of the country`s Railways as a result of industry restructuring during the period from 2001 till 2010. It clarifies the reason for the absence of sector targets` achievement, which were set by the concept of reform of the 1998th year, the results of the reforms are assessed in the countries of the European Union.